Adoptive T cell therapy: engineering and biomanufacturing chimeric antigen receptor-T cell. (December 2018) - Jenkins, Jackson; Park, Jaeyoung; Petersen, Kristen; Shajihan, Kahmil; Kruthiventi, Srivalli; Betenbaugh, Michael
Graphical abstract: Highlights: The parameters for CAR-T cell manufacturing should be optimized for scale-up. Correct control of key parameters is crucial for high concentrations of CAR T cells. Engineered CAR-T cells secreting armor agents are promising in treating tumor cells. Abstract : Development of Chimeric Antigen Receptor (CAR)-T cells is revolutionizing the field of cell therapy. Since its inception, research has been focused on improving the effectiveness, accessibility, and safety of CAR-T cell therapy. To achieve this, the biomanufacturing process must be scaled and optimized to match increasing demand. The current processes of engineering, activating, expanding, and purifying CAR-T cells have improved in recent years, but significant challenges in process scaleup and consistency remain. Additionally, engineering efforts now aim to enhance CAR-T cell therapy with 'armored' CAR-T cells to improve solid tumor penetration and immune system response to cancer. This review highlights the current processes and challenges in biomanufacturing and engineering CAR-T cells to improve its success in cancer treatment.